Distroâ: Independent Creativity for Independent Industr - Wulandari, Wiwik Sri (Journal of Urban Societys Arts, 2012)
To shortened this introduction, âDistroâ is one of cultural phenomenon in theyoung generation nowadays. The word of âDistroâ is the shortened of DistributionOutlet. The phenomenon of âDistroâ has been some kind of new trends inproducing and distributing creative design products of goods amongst theyoungsters independently, in an independence industry that open for challengingand competitiveness for everyone. This field research has been done in the city ofYogyakarta, reknown as the second city in creative design products after the cityof Bandung. Yogyakarta is welknown as the studentsâ city as well as the capital cityof culture of Indonesia. As a studentsâ city it is normal that Yogyakarta is growingin numbers of young people who pursued to study here and enriched the cultureof the city to become more multicultural and the varieties of pluralism as well.This sociocultural phenomenon not only brought some dynamic changing tosociety, economy and cultural life of the city, but also social problems that needsto be overcome. My first research question then is about how the existence ofâDistroâ in Yogyakarta can be a positive answer for social problems that may arisesfrom the hegemony of globalization markets domestically? My second questionis how the creative product designs are being made and distributed creatively inindependent industry? Lastly, my third question is dealling with the genres ofthe design products and how it can be a new trend in art expression? âDistroâ is aproduct of culture and it is also creating cultural change in some aspects of the lifeof the youngsters who are âDistroâ enthusiasts. âDistroâ phenomenon basically is anoffensive to the hegemony of internationally branded product design which turnsto become more over-dominated to the domestic markets and industry and thus,âDistroâ has the spirit of survival whilts at the same time producing opportunity ofenterpreneurship.Â âDistroâ: Kreativitas Independen untuk Industri Independen. Distro (DistributionOutlet) adalah salah satu fenomena yang terjadi pada generasi muda dewasa ini.Distro telah menjadi sebuah tren baru dalam memproduksi dan mendistribusikanbarang-barang dengan desain yang kreatif. Kaum muda melakukannya secaraindependen di dalam sebuah industri yang independen di mana siapapun ditantanguntuk terlibat dalam persaingan. Penelitian ini dilakukan di Yogyakarta, kota kreatifkedua setelah Bandung. Kota ini dikenal sebagai kota pelajar dan kota budaya.Sejumlah besar pemuda datang dari seluruh Indonesia ke kota ini untuk belajar. Halini menyebabkan munculnya multikulturalitas dan pluralitas. Fenomena sosiokulturalini tidak saja menghadirkan dinamika dalam bidang ekonomi dan budaya, namunjuga masalah-masalah sosial yang harus dipecahkan. Masalah-masalah penelitianÂ yang akan dijawab dengan penelitian ini adalah: pertama, bagaimana keberadaan Distro diYogyakarta dapat menjawab masalah-masalah social yang muncul karena hegemono pasarglobal?; kedua, bagaimana produk-produk dengan desain kreatif dibuat dan didistribusikansecara kreatif di dalam industri independen?; ketiga, apa saja genre desain produk yangdihasilkan dan bagaimana genre tersebut bisa menjadi sebuah tren baru dalam ekspresi seni?Distro adalah sebuah produk budaya yang juga menimbulkan perubahan budaya di kalanganpendukungnya. Fenomena Distro pada dasarnya adalah sebuah serangan terhadap hegemonidesain produk dengan merk internasional yang semakin lama semakin mendominasi pasardan industri domestic sehingga dengan demikian, Distro memancarkan semangat untukbertahandan pada saat yang sama menciptakan peluang-peluang kewirausahaan.